The effect of age of regrowth on content and release of manganese, iron, zinc and copper from four tropical forages incubated in sacco in rumen of sheep - Kabaija, E.; Smith, O.B. (Elsevier, 1988)
Investigates the changes due to age of regrowth on mineral content of four tropical forages and release of these minerals in sacco in the rumen of sheep.